The Potential of Calliandra (Calliandra calothyrus) As Conservation Plants Based on Economic Analysis - Afrrah Junita; Puti Andiny (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Kaliandra (Calliandra calothyrsus) is a leguminous plant native to Central America, belonging to the Fabaceae (Leguminosae) family. This plant is a multipurpose species known as a source of high-quality forage for livestock and mostly used for soil conservation. Therefore, Kaliandra is suitable for businesses in both plantation and livestock sectors. Primary data collection was conducted through field observations, captured in digital form (photos or images), and interviews with representative sources. Secondary data were obtained from literature reviews related to theories underlying the background and problem formulation, reviews of official documents or archives from the Seed Control Agency of the Department of Agriculture and Plantations in Aceh regarding the physical and non-physical data of the study objects, as well as journals, internet sources, and others. The financial feasibility analysis of the kaliandra business was conducted by calculating the Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C), and Internal Rate of Return (IRR) using a discount factor of 10%. The results showed an NPV of IDR 416,538,245.51 (NPV > 0). Additionally, the B/C ratio was calculated to be 6.2 (B/C > 1), and the IRR was 12.3% (IRR > i). Based on these calculations, all evaluation criteria were met: NPV is positive, B/C is greater than 1, and IRR is 12.3%, which is higher than the Opportunity Cost of Capital of 10%. Thus, it can be concluded that the development of kaliandra (Calliandra calothyrsus) business is profitable and feasible.